Brazilian recommendations of mechanical ventilation 2013. Part 2 (Jornal brasileiro de pneumologia, 2014)
Perspectives on invasive and noninvasive ventilatory support for critically ill patients are evolving, as much evidence indicates that ventilation may have positive effects on patient survival and the quality of the care provided in intensive care units in Brazil. For those reasons, the Brazilian Association of Intensive Care Medicine (Associação de Medicina Intensiva Brasileira - AMIB) and the Brazilian Thoracic Society (Sociedade Brasileira de Pneumologia e Tisiologia - SBPT), represented by the Mechanical Ventilation Committee and the Commission of Intensive Therapy, respectively, decided to review the literature and draft recommendations for mechanical ventilation with the goal of creating a document for bedside guidance as to the best practices on mechanical ventilation available to their members. The document was based on the available evidence regarding 29 subtopics selected as the most relevant for the subject of interest. The project was developed in several stages, during which the selected topics were distributed among experts recommended by both societies with recent publications on the subject of interest and/or significant teaching and research activity in the field of mechanical ventilation in Brazil. The experts were divided into pairs that were charged with performing a thorough review of the international literature on each topic. All the experts met at the Forum on Mechanical Ventilation, which was held at the headquarters of AMIB in São Paulo on August 3 and 4, 2013, to collaboratively draft the final text corresponding to each sub-topic, which was presented to, appraised, discussed and approved in a plenary session that included all 58 participants and aimed to create the final document. O suporte ventilatório artificial invasivo e não invasivo ao paciente grave tem evoluído e inúmeras evidências têm surgido, podendo ter impacto na melhora da sobrevida e da qualidade do atendimento oferecido nas unidades de terapia intensiva no Brasil. Isto posto, a Associação de Medicina Intensiva Brasileira (AMIB) e a Sociedade Brasileira de Pneumologia e Tisiologia (SBPT) - representadas por seu Comitê de Ventilação Mecânica e sua Comissão de Terapia Intensiva, respectivamente, decidiram revisar a literatura e preparar recomendações sobre ventilação mecânica, objetivando oferecer aos associados um documento orientador das melhores práticas da ventilação mecânica na beira do leito, com base nas evidências existentes, sobre os 29 subtemas selecionados como mais relevantes no assunto. O projeto envolveu etapas que visaram distribuir os subtemas relevantes ao assunto entre experts indicados por ambas as sociedades, que tivessem publicações recentes no assunto e/ou atividades relevantes em ensino e pesquisa no Brasil, na área de ventilação mecânica. Esses profissionais, divididos por subtemas em duplas, responsabilizaram-se por fazer uma extensa revisão da literatura mundial. Reuniram-se todos no Fórum de Ventilação Mecânica, na sede da AMIB, na cidade de São Paulo (SP), em 3 e 4 de agosto de 2013, para finalização conjunta do texto de cada subtema e apresentação, apreciação, discussão e aprovação em plenária pelos 58 participantes, permitindo a elaboração de um documento final.